Time dependency in the radiofrequency lesion formation for a local impedance guided catheter in an ex vivo experimental model - Daisuke Kawano; Hitoshi Mori; Kenta Tsutsui; Hidehira Fukaya; Naomichi Tanaka; Masataka Narita; Wataru Sasaki; Kazuhisa Matsumoto; Yoshifumi Ikeda; Takahide Arai; Shintaro Nakano; Ritsushi Kato (Journal of Arrhythmia, 2022)
Abstract Background The local impedance (LI) is an emerging technology that monitors tissue‐catheter coupling during radiofrequency (RF) ablation. The relationships between the LI, RF delivery time, and lesion formation remain unclear. Methods Using an LI‐enabled RF catheter in an ex vivo experimental model, RF lesions were created combined with various steps in the power (40 and 50 W), CF (10 g, 30 g, and 50 g), and time (10s, 20s, 30s, 40s, 50s, and 60s at 40 W and 5 s, 10s, 20s, 30s, 40s, 50s, and 60s at 50 W). The correlations between the LI drop, lesion size, and RF delivery time were evaluated. The rate of change in the time‐dependent gain in the LI, depth, and diameter and the time to reach 90% decay of the peak dY/dT (time to 90% decay) were assessed. Results The correlation between the LI drop and ablation time revealed non‐linear changes. The time to a 90% decay in the LI drop differed depending on the RF ablation setting and was always shorter with the 50 W setting than 40 W setting. The LI drop always correlated with the lesion formation under all ablation power settings. Deeper or wider lesions were predominantly created within the time to 90% decay of the LI drop. Conclusion The LI drop was useful for predicting lesion sizes. Deeper or wider lesions cannot be obtained with a longer ablation than the 90% decay time of the LI drop. A shorter ablation than the 90% decay time of the LI drop would be preferable for an effective ablation.